Price and non-price competition interactions: Implicit pricing of network size and differentiation effects - Jared Osoro; Kiplangat Josea (Kenya Bankers Association (KBA), 2021)
Contrary to predictions that brick-and-mortar banking declines with increased financial innovations and technological adoptions, bank branch network between 2006 and 2018 has tripled and ATM networks have increased four-fold. In this paper, we examine whether network convenience matter for price competition. Using a panel data framework over the 2006 to 2019 period for thirty-eight commercial banks, we find that non-price competition indicators matter for the bank's pricing behaviour. In particular: (i) the provision of an extensive branch network is associated with a higher operating costs per unit of deposits, a 'shadow price' of deposits, but is not directly priced in the case of ATMs network; (ii) the effect of network convenience on the deposit rate is negative for both bank branch network and ATMs network albeit insignificant, while the a higher deposit to branch network ratio is associated with a significant reduction in the deposit rate and but seems to be offset by a higher labour to branch network ratio, with the net effect being positive thus suggesting that deposit rates tend to rise with increased network convenience; (iii) a more extensive branch network and a higher labour-to-branch staffing ratio are significantly associated with higher loan rate, while inversely and significantly associated with a higher depositto-branch network ratio suggesting that the benefits of higher branch output productivity (and revenues) is passed on to borrowers in the form of a lower loan rates; (iv) differences in bank branch and ATMs significantly affects fee income albeit inversely in the case of branch network and positively in the case of ATMs network.
Keywords: 330; Banks; Competition; Branch; ATMs; Pricing Behaviour